The Influence Of Social Media On Students’ Habits In Speaking Indonesian - Yeni Eriska Sihotang; Nur Idaman Lase; Cindy Aurellia; Kristina Sipayung; Amelia Stevani Hutagalung (Outline Publisher, 2025)
At present, social media has developed into one of the most common communication tools used by university students. The use of social media platforms not only shapes the way individuals engage socially with one another but also leaves a significant impact on their linguistic practices, particularly in relation to the Indonesian language. The purpose of this study is to examine how social media influences students’ language habits when using Indonesian, both in written and spoken forms. A descriptive qualitative approach was employed, collecting data through observation and questionnaires administered to a group of students. The findings reveal that students who frequently use social media tend to adopt non-standard language, abbreviations, and code-mixing with foreign languages, which gradually has the potential to undermine their ability to communicate effectively and correctly in Indonesian. Nevertheless, social media also presents beneficial prospects, such as fostering greater creativity in sentence construction, expanding vocabulary, and cultivating a stronger interest in writing. Consequently, social media exerts a dual influence on students’ language behavior, encompassing both positive and negative aspects, thereby underscoring the need for awareness and the cultivation of Indonesian language use that adheres to established linguistic norms.